Adipose Dicer-1 modulates systemic insulin signaling and longevity via a miR-8–Aop–Dilp6 axis - María C. Ingaramo; Francisco Ramello; Silvano J. Santander; Yemina Abelendo; Andrés Dekanty (Proceedings of the National Academy of Sciences, 2026)
Interorgan communication is essential for metabolic homeostasis and healthy aging, with adipose tissue acting as a central hub that coordinates systemic metabolism, stress responses, and longevity. Here, we show that the miRNA-processing enzyme Dicer-1 (Dcr-1) acts in the fat body (FB) to regulate Dilp2 secretion from brain insulin-producing cells (IPCs), thereby modulating systemic insulin signaling and lifespan in Drosophila . Dcr-1 expression is reduced in multiple long-lived conditions, and its partial downregulation enhances oxidative stress resistance, alters lipid metabolism, and extends lifespan even under dietary restriction. Proteomic profiling of FBs from Dcr-1 heterozygous flies revealed widespread metabolic reprogramming and stress adaptation consistent with attenuated insulin/IGF signaling (IIS). Mechanistically, reduced Dcr-1 lowers miR-8 levels in the FB, which indirectly upregulates Drosophila insulin-like peptide 6 (Dilp6). Dilp6 acts nonautonomously to suppress Dilp2 secretion from IPCs, reducing systemic IIS and promoting longevity. We further show that Dcr-1 reduction activates the ETS-family repressor Aop/ETV6 downstream of Ras-Erk signaling, which is required for Dilp6 induction and the lifespan extension observed upon miR-8 depletion. Collectively, these findings reveal a miRNA-dependent regulatory axis that couples adipose-derived endocrine signals to systemic insulin regulation and aging, positioning Dcr-1 as a central node in the control of metabolic homeostasis and lifespan.